Dampak bermain game online terhadap pelajar: A scoping review - Maulana, Ahmed Akas; Mutiara R., Dwika; Hifdlil W, Hilya; Asrofi, Nur M. (Maliki Interdisciplinary Journal, 2025)
This study aims to investigate the impact of playing online games on students academic performance, physical and mental health, and social environment. The method used was a scoping review using the PRISMA approach, with 30 relevant articles selected based on inclusion and exclusion criteria. The results of this study show that improving English language skills, time management skills, and attention and concentration can provide good results. However, there are also drawbacks, including low academic performance, physical health problems such as insomnia and poor posture, and psychological illnesses including addiction and emotional instability. Suggested solutions include socialization, education and self-control with the support of parents, schools and the community to help students find a balance between real conditions and the digital world.